Response inhibition and interference control in patients with bipolar I disorder and first‐degree relatives. (29th September 2015) - Hıdıroğlu, Ceren; Torres, Ivan J; Er, Ayşe; Işık, Gizem; Yalın, Nefize; Yatham, Lakshmi N; Ceylan, Deniz; Özerdem, Ayşegül
Abstract : Objectives: The current study aimed to assess both response inhibition (RI) and interference control (IC) in euthymic patients with bipolar disorder (BD‐Ps) as well as asymptomatic first‐degree relatives (BD‐Rs) and healthy controls (HCs) in order to evaluate trait‐as opposed to illness‐associated features of these components. Methods: BD‐Ps (n = 35) who had been in the euthymic state for at least six months, BD‐Rs (n = 30), and HCs (n = 33) completed a Stop‐Signal Task (SST) and Stroop Task to assess RI and IC, respectively. Groups were compared on the stop‐signal reaction time (SSRT), stop‐signal delay (SSD), mean reaction time on go trials (go‐RT), Stroop interference score (S‐interference), and number of errors on the color–word‐naming trial (S‐error). Associations between the patient's clinical features and RI and IC, between the patient's treatment and RI and IC, and between RI and IC in each group were investigated. Results: BD‐Ps and BD‐Rs had significantly shorter go‐RT and SSD, and longer SSRT compared to HCs, with these scores being similar between the BD‐Ps and BD‐Rs. Also, both BD‐Ps and BD‐Rs made significantly more S‐errors than HCs, whereas, the S‐interference score was not significantly different between groups. There were no significant correlations between Stroop Task and SST scores within each group, nor between clinical features or treatment variables and RI and IC in BD‐Ps. Conclusions: Overall, impairment in RI and IC (only on S‐error score) was present in both patients and relatives. The persistence of these deficits in the absence of mood symptoms suggests that these features may represent candidate endophenotypes for bipolar disorder.